Gaya Kepemimpinan, Kepuasan Kerja dan Ketakutan akan COVID-19 Para Perawat - Gusrina Komara Putri; Moh. Heri Kurniawan (FORIKES, 2022)
Nurses as the largest component of the workforce dealing with COVID-19 patients experienced changes in leadership styles and also changes in job satisfaction, and felt fear in dealing with COVID-19 patients. This study aims to examine the relationship between leadership style and job satisfaction and nurses' fear of COVID-19. A cross-sectional design was used in this study using three types of questionnaires, namely the Multifactorial Leadership Questionnaire, the Minnesota Satisfaction Questionnaire and the Fear of COVID-19. In addition, demographic characteristics were also added. Respondents obtained as many as 266 people. The data were analyzed descriptively and continued with hypothesis testing. The results showed that there was a relationship between leadership style and job satisfaction for nurses who served in the COVID-19 Room (p = 0.439). In addition, nurses' fear of COVID-19 tends to be low compared to other countries.Keywords: COVID-19; leadership style; job satisfaction; fear of COVID-19ABSTRAK Para perawat sebagai komponen tenaga terbesar yang menangani pasien COVID-19 mengalami perubahan gaya kepemimpinan dan juga perubahan kepuasan kerja, serta merasakan ketakutan dalam menangani pasien COVID-19. Penelitian ini bertujuan untuk melihat hubungan antara gaya kepemimpinan dengan kepuasan kerja dan ketakutan para perawat akan COVID-19. Desain cross-sectional digunakan pada penelitian ini dengan menggunakan tiga jenis kuisioner yaitu Multifactorial Leadership Questionnaire, Minnesota Satisfaction Questionnaire dan Ketakutan akan COVID-19. Selain itu karakteristik demografi juga ditambahkan. Responden didapatkan sebanyak 266 orang. Data dianalisis secara deskriptif dan dilanjutkan dengan pengujian hipotesis. Hasil penelitian menunjukkan adanya hubungan antara gaya kepemimpinan dan kepuasan kerja pada perawat yang berdinas di Ruang COVID-19 (p = 0.439). Selain itu, ketakutan perawat terhadap COVID-19 cenderung rendah dibandingkan dengan negara lain.Kata kunci: COVID-19; gaya kepemimpinan; kepuasan kerja; ketakutan akan COVID-19